Coalition‐Proof Trade and the Friedman Rule in the Lagos‐Wright Model - Hu, Tai‐wei; Kennan, John; Wallace, Neil (Journal of Political Economy, 2009)
The Lagos‐Wright model—a monetary model in which pairwise meetings alternate in time with a centralized meeting—has been extensively analyzed, but always using particular trading protocols. Here, trading protocols are replaced by two alternative notions of implementability: one that allows only individual defections and one that also allows cooperative defections in meetings. It is shown that the first‐best allocation is implementable under the stricter notion without taxation if people are sufficiently patient. And, if people are free to skip the centralized meeting, then lump‐sum taxation used to pay interest on money does not enlarge the set of implementable allocations.